Implementasi Metode Pengajaran Berdasarkan Ulangan 6:4-9 bagi Perkembangan Spiritualitas Anak Usia Dini - Syani Bombongan Rante Salu (Didache: Journal of Christian Education, 2022)
The purpose of this research is to find the teaching method contained in Deuteronomy 6:4-9 that can reach all realms to achieve early childhood spiritual development. With qualitative methods and analysis with a literature approach which then uses descriptive and analytical methods on the texts in the Bible, it can be found that early age is the golden age in which it is very easy to instill teaching for them. In Deuteronomy 6:4-9 it is found that several methods can reach 3 domains, namely the cognitive realm by teaching repeatedly, affective by always paying attention, namely by placing in the heart and soul, and the psychomotor realm by communicating with the child at all times, and marker method for systematic learning. The implementation of these three methods is very effective in the development of early childhood spirituality because it involves cognitive, affective, and psychomotor.